Third party assessment of resection margin status in head and neck cancer. (June 2016) - Ransohoff, Amy; Wood, Douglas; Solomon Henry, A.; Divi, Vasu; Colevas, A.
Highlights: HNC margins status determination methods are not well defined in prior reports. 20% of margins from head and neck cancer resections can't be determined with chart review. Improvement in methods for surgical margin documentation are needed. Inability to define margins on audit hampers research. Summary: Background: Definitive assessment of primary site margin status following resection of head and neck cancer is necessary for prognostication, treatment determination and qualification for clinical trials. This retrospective analysis determined how often an independent reviewer can assess primary tumor margin status of head and neck cancer resections based on review of the pathology report, surgical operative report, and first follow-up note alone. Methods: We extracted from the electronic medical record pathology reports, operative reports, and follow-up notes from head and neck cancer resections performed at Stanford Hospital. We classified margin status as definitive or not. We labeled any pathology report clearly indicating a positive, negative, or close (<5 mm) margin as definitive. For each non-definitive pathology report, we reviewed the operative report and then the first follow-up note in an attempt to clarify margin status. We also looked for associations between non-definitive status and surgeon, year, and primary site. Results: 743 unique cases of head and neck cancer resection were extracted. We discarded 255 as non-head and neck cancer cases, or cases that did not involve a definitive resection of a primary tumor site. We could not definitively establish margin status in 20% of resections by independent review of the medical record. There was no correlation between margin determination and surgeon, site, or year of surgery. Conclusion: A substantial fraction (20%) of primary site surgical margins could not be definitively determined via independent EMR review. This could have implications for subsequent patient care decisions and clinical trial options.